Sociodemographic, behavioral and genetic determinants of allostatic load in a Swiss population-based study. (May 2016) - Petrovic, Dusan; Pivin, Edward; Ponte, Belen; Dhayat, Nasser; Pruijm, Menno; Ehret, Georg; Ackermann, Daniel; Guessous, Idris; Younes, Sandrine Estoppey; Pechère-Bertschi, Antoinette; Vogt, Bruno; Mohaupt, Markus; et al.
Highlights: Allostatic load (AL) is a measure of generalized physiological dysregulation. We investigated the associations between environmental and genetic factors and AL. SES and lifestyle factors determined AL, but this association was dependent on sex. Heritability of AL was estimated to 29.5%. Allostatic load is determined by both environmental and genetic factors SES: Socioeconomic status Abstract: Allostatic load (AL) is a marker of physiological dysregulation which reflects exposure to chronic stress. High AL has been related to poorer health outcomes including mortality. We examine here the association of socioeconomic and lifestyle factors with AL. Additionally, we investigate the extent to which AL is genetically determined. We included 803 participants (52% women, mean age 48 ± 16 years) from a population and family-based Swiss study. We computed an AL index aggregating 14 markers from cardiovascular, metabolic, lipidic, oxidative, hypothalamus-pituitary-adrenal and inflammatory homeostatic axes. Education and occupational position were used as indicators of socioeconomic status. Marital status, stress, alcohol intake, smoking, dietary patterns and physical activity were considered as lifestyle factors. Heritability of AL was estimated by maximum likelihood. Women with a low occupational position had higher AL (low vs. high OR = 3.99, 95%CI [1.22;13.05]), while the opposite was observed for men (middle vs. high OR = 0.48, 95%CI [0.23;0.99]). Education tended to be inversely associated with AL in both sexes(low vs. high OR = 3.54, 95%CI [1.69;7.4]/OR = 1.59, 95%CI [0.88;2.90] in women/men). Heavy drinking men as well as women abstaining from alcohol had higher AL than moderate drinkers. Physical activity was protective against AL while high salt intake was related to increased AL risk. The heritability of AL was estimated to be 29.5% ±7.9%. Our results suggest that generalized physiological dysregulation, as measured by AL, is determined by both environmental and genetic factors. The genetic contribution to AL remains modest when compared to the environmental component, which explains approximately 70% of the phenotypic variance.